Is It Safe to Combine a Fundoplication to Sleeve Gastrectomy? Review of Literature - Carandina, Sergio (Medicina (Kaunas), 2021)
Background and Objectives: The rising numbers of laparoscopic sleeve gastrectomy (LSG) procedures now being performed worldwide will likely be followed by an increasing number of patients experiencing gastro-esophageal reflux disease (GERD). The purpose of the current review was to analyze in terms of safety different techniques of fundoplication used to treat GERD associated with LSG. Methods: An online search was performed in PubMed/MEDLINE in December 2020 to identify articles reporting LSG and fundoplication. The following term combination was used: (sleeve, fundoplication), (sleeve, Nissen), (sleeve, Rossetti), (sleeve, Toupet) and (sleeve, Dor). The extracted information included details of the methods (e.g., retrospective case series), demographic characteristics (e.g., age, gender), clinical characteristics, number of patients, rate of conversion, and postoperative outcomes. Results: A total of 154 studies were identified and after an assessment of title according to our exclusion criteria, 116 articles were removed. Of the 38 studies analyzed for full content review, a total of seven primary studies (487 patients) were identified with all inclusion criteria. Analyzing the different types of fundoplication used, we have identified: 236 cases of Nissen-Sleeve, 220 cases with modified Rossetti fundoplication, 31 cases of Dor fundoplication, and no case of Toupet fundoplication. The overall postoperative complication rate was 9.4%, with the most common reported complication being gastric perforation, 15 cases—3.1%. The second most common complication was bleeding identified in nine cases (1.8%) followed by gastric stenosis in six cases (1.2%). The mortality was nil. Conclusions: Different types of fundoplication associated with LSG appear to be a safe surgical technique with an acceptable early postoperative complication rate. Any type of fundoplication associated with LSG to decrease GERD should be evaluated cautiously while prospective clinical randomized trials are needed.